Uma abordagem comparativa da ironia: conceito, tropo e performance - Maas, Wilma Patricia Marzari Dinardo [UNESP] (My University, 2010)
We pursue in this paper an understanding of irony which is shared by both the German author Friedrich Schlegel and the critic Paul de Man. Irony is rather understood as a trope and as a performative act than as a concept, which has indeed consequences to the very legibility of texts.

No presente artigo identificamos uma compreensão da ironia que é comum ao primeiro-romântico alemão Friedrich Schlegel e ao crítico Paul de Man. Nessa linhagem, a ironia é entendida antes como tropo e performance do que como conceito, o que tem consequências para a própria legibilidade do discurso.
A comparative approach of irony as concept, trope and performance
Keywords: Irony; Paul de Man; Friedrich Schlegel; Ironia; Friedrich Schlegel; Paul de Man